A geometrical criterion for nonexistence of constant-sign solutions for some third-order two-point boundary value problems - Smirnov, Sergey (Nonlinear Analysis: Modelling and Control, 2020)
We give a simple geometrical criterion for the nonexistence of constant-sign solutions for a certain type of third-order two-point boundary value problem in terms of the behavior of nonlinearity in the equation. We also provide examples to illustrate the applicability of our results.
Keywords: third-order two-point boundary value problems; nonexistence of solutions; comparison methods for the first zero functions